Stress concentration factors in CHS-CFSHS T-joints: Experiments, FE analysis and formulae. (15th November 2017) - Tong, L.W.; Xu, G.W.; Yang, D.L.; Mashiri, F.R.; Zhao, X.L.
Highlights: We tested hot spot stress distribution in CHS-CFSHS T-joints. We established finite element models for CHS-CFSHS T-joints. We investigated influences of non-dimensional parameters on SCF in CHS-CFSHS T-joints. We proposed SCF formulae for CHS-CFSHS T-joints. Abstract: A CHS-CFSHS T-joint is fabricated by welding a circular hollow section (CHS) brace to a concrete-filled square hollow section (CFSHS) chord. This paper presents an investigation into stress concentration factors (SCFs) of CHS-CFSHS T-joints through experimental testing as well as finite element (FE) analysis. A series of well-designed CHS-CFSHS T-joints are first tested under axial loading (tension and compression respectively) and in-plane bending in the brace so that the strain concentration factors (SNCFs) of the joints are determined. By comparing the experimental results with those extracted from previous research on empty CHS-SHS T-joints, it is found that the in-filled concrete can effectively reduce the maximum SNCF and therefore SCF. Three-dimensional FE models are subsequently developed and validated. Then an extensive parametric study is conducted to evaluate the influences of three key non-dimensional geometric parameters (i.e. β, 2 γ and τ ) using the validated FE modeling strategy. Finally, SCF formulae corresponding to typical load conditions are established for fatigue design of CHS-CFSHS T-joints.